Protease-Activated Receptors Upregulate Cyclooxygenase-2 Expression in Human Endothelial Cells - Houliston, Rebecca A.; Keogh, Rosemary J.; Sugden, David; Dudhia, Jayesh; Carter, Tom D.; Wheeler-Jones, Caroline P. D. (Thrombosis and Haemostasis, 2002)
We have previously shown that the serine protease thrombin and other G protein-coupled agonists acutely enhance synthesis and release of prostacyclin from human umbilical vein endothelial cells (HUVEC) through activation of cPLA2α. Here, we show that thrombin and other physiological endothelial cell agonists upregulate COX-2 induction in HUVEC. Thrombin treatment caused a rapid and sustained increase in prostacyclin (PGI2) synthesis from HUVEC. Thrombin and a selective protease-activated receptor-1 (PAR-1) peptide (TRAP) evoked doseand time-dependent increases in COX-2 protein expression which were equivalent to that induced by the proinflammatory cytokine IL-1α. Quantitative and real-time PCR analysis showed enhanced COX-2 mRNA expression in thrombinor TRAP-stimulated HUVEC whereas COX-1 expression was unaffected. A PAR-2 agonist peptide also induced COX-2 protein and mRNA expression with kinetics distinct from those of thrombin, and promoted PGI2 release. These results demonstrate that regulation of COX-2 induction is an important functional response of HUVEC to PAR activation and suggest that PARs promote sustained upregulation of prostanoid production in human endothelium.
Keywords: Human endothelium; thrombin; cyclooxygenase; prostacyclin; protease-activated receptors